A ratiometric fluorescent sensor for Al3+ and Cu2+ detection in food samples - Li, Mo; Chen, Xueguo; Xia, Xinxin; Zhang, Ting; Zhang, Wenji; Xu, Qingxin; Zhao, Xin (Frontiers in Nutrition, 2025)
ObjectiveAluminum (Al) and copper (Cu), as two common elements, have specific applications in the modern food industry. However, excessive levels of Al3+ and Cu2+ pose a major risk to ecosystems and human health. Thus, fast, sensitive, and portable detection technologies are indispensable for achieving source control of such hazardous substances.MethodsWe synthesized GSH-stabilized gold nanoclusters (G-AuNCs) and Nitrogen-doped graphene quantum dots (N-GQDs) via a straightforward hydrothermal method, and constructed GQDs@AuNCs ratiometric fluorescent sensors through electrostatic interactions for the rapid detection of Al3+ and Cu2+ in food samples.ResultsWhen the concentration of Al3+ in the reaction medium increases, the fluorescence intensity (FI) of G-AuNCs incrementally enhances; in contrast, when the concentration of Cu2+ increases, the FI of G-AuNCs is gradually quenched. Notably, the FI of N-GQDs remains unchanged throughout this process. When the concentrations of Al3+ and Cu2+ ions are within the ranges of 0.5–500 μM and 1–200 μM, respectively, the FI ratio (I528/I412)/(I528/I412)0 shows a strong linear correlation with the ion concentrations, with corresponding limits of detection (LOD) of 0.66 μM and 0.44 μM.ConclusionThe fluorescent sensor features simple synthesis, rapid detection, and high sensitivity, making it well-suited for the rapid detection of Al3+ and Cu2+ in foods such as fried dough twists and shellfish.